2023
DOI: 10.1182/blood.2022018849
|View full text |Cite
|
Sign up to set email alerts
|

C1 inhibitor deficiency enhances contact pathway mediated activation of coagulation and venous thrombosis

Abstract: C1 inhibitor (C1INH) is a multifunctional serine protease inhibitor that functions as a major negative regulator of several biological pathways, including the contact pathway of blood coagulation. In humans, congenital C1INH deficiency results in a rare episodic bradykinin-mediated swelling disorder called hereditary angioedema (HAE). Patients with C1INH deficiency associated HAE (C1INH-HAE) have increased circulating markers of activation of coagulation. Further, we recently reported that patients with C1INH-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…A proteome-wide MR study based on 81 669 VTE cases of multiple ancestries identified 23 proteins associated with VTE [ 4 ], many of which were confirmed in our study, such as those for coagulation FXI, prekallikrein, prothrombin, and protein S with well-defined function in thrombosis. Consistent with findings from another protein-wide study [ 29 ], we also identified associations of VTE with genetically predicted levels of kininogen 1 and protein C. For other identified proteins in relation to thrombosis in our MR analysis, we noticed supporting evidences from previous studies on phospholipase C gamma 2 (PLCG2) [ 30 ], ANGPT1 [ 31 , 32 ], glycoprotein VI (GPVI) [ 33 ], tyrosine kinase Syk (SYK) [ 34 ], N-terminal pro-BNP [ 35 ], metalloproteinase inhibitor 3 (TIMP-3) [ 36 ], extracellular matrix protein 1 (ECM1) [ 37 ], ADAMTS-13 [ 38 ], protease nexin-1 (SERPINE2) [ 39 ], annexin II [ 40 ], IL-6 sRa [ 41 ], plasma protease C1 inhibitor [ 42 ], fibrinogen g-chain dimer [ 43 ], Trem-like transcript 1 protein [ 44 ], ubiquitin-associated and SH3 domain–containing protein B (UBASH3B, also known as T-cell ubiquitin ligand 2) [ 45 ], and regulator of G-protein signaling 18 (RGS18) [ 46 ]. Despite limited direct evidence linking VTE with LPR12, this lipid metabolism–related protein has been associated with platelet internalization [ 47 ] and vascular endothelial function [ 48 ], which thus may be indirectly associated with thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…A proteome-wide MR study based on 81 669 VTE cases of multiple ancestries identified 23 proteins associated with VTE [ 4 ], many of which were confirmed in our study, such as those for coagulation FXI, prekallikrein, prothrombin, and protein S with well-defined function in thrombosis. Consistent with findings from another protein-wide study [ 29 ], we also identified associations of VTE with genetically predicted levels of kininogen 1 and protein C. For other identified proteins in relation to thrombosis in our MR analysis, we noticed supporting evidences from previous studies on phospholipase C gamma 2 (PLCG2) [ 30 ], ANGPT1 [ 31 , 32 ], glycoprotein VI (GPVI) [ 33 ], tyrosine kinase Syk (SYK) [ 34 ], N-terminal pro-BNP [ 35 ], metalloproteinase inhibitor 3 (TIMP-3) [ 36 ], extracellular matrix protein 1 (ECM1) [ 37 ], ADAMTS-13 [ 38 ], protease nexin-1 (SERPINE2) [ 39 ], annexin II [ 40 ], IL-6 sRa [ 41 ], plasma protease C1 inhibitor [ 42 ], fibrinogen g-chain dimer [ 43 ], Trem-like transcript 1 protein [ 44 ], ubiquitin-associated and SH3 domain–containing protein B (UBASH3B, also known as T-cell ubiquitin ligand 2) [ 45 ], and regulator of G-protein signaling 18 (RGS18) [ 46 ]. Despite limited direct evidence linking VTE with LPR12, this lipid metabolism–related protein has been associated with platelet internalization [ 47 ] and vascular endothelial function [ 48 ], which thus may be indirectly associated with thrombus formation.…”
Section: Discussionmentioning
confidence: 99%
“…This begs the question why do thrombotic events appear to infrequent in HAE patients during acute episodes of angioedema. 111,112 This might be explainable if bradykinin production in HAE is partly, or even largely, surface-independent. The mechanism by which DFXII310 causes HAE, at the very least, demonstrates that surface-mediated contact activation is not an absolute requirement for symptomatic HAE.…”
Section: Discussionmentioning
confidence: 99%
“…The mouse IVC stenosis model of DVT was performed in mice, as previously described. 4,[16][17][18] Only male mice were used for this model, as ligation in female mice may result in necrosis of the reproductive organs. 17,19 Briefly, a midline laparotomy was made, IVC side branches were first ligated.…”
Section: Inferior Vena Cava (Ivc) Stenosis Modelmentioning
confidence: 99%